2015
DOI: 10.4049/jimmunol.1500373
|View full text |Cite
|
Sign up to set email alerts
|

Essential Function for the Nuclear Protein Akirin2 in B Cell Activation and Humoral Immune Responses

Abstract: Akirin2, an evolutionarily conserved nuclear protein, is an important factor regulating inflammatory gene transcription in mammalian innate immune cells by bridging the NF-κB and SWI/SNF complexes. Although Akirin is critical for Drosophila immune responses, which totally rely on innate immunity, the mammalian NF-κB system is critical not only for the innate but also for the acquired immune system. Therefore, we investigated the role of mouse Akirin2 in acquired immune cells by ablating Akirin2 function in B l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…This is a finding reminiscent of our prior work on corticogenesis (Bosch et al, ), where we showed that massive cell death occurred in the telencephalon within 12 hr after Emx1‐Cre ‐mediated Aki2 deletion. In addition, other studies suggest that an important functional role for Aki2 occurs during rapid proliferation of cells in response to a stimulus (Komiya, Akiyama, Sakumoto, & Tashiro, ; Komiya et al, ; Tartey et al, ), consistent with our observations. In contrast, our knockdown experiments using shRNA against Aki2 in differentiating C2C12 cells did not cause any obvious cell death, and the presence of persistent tdTom‐positive cells in Aki2 SimKO mutants suggests that not all cells die when Aki2 is removed.…”
Section: Discussionsupporting
confidence: 92%
“…This is a finding reminiscent of our prior work on corticogenesis (Bosch et al, ), where we showed that massive cell death occurred in the telencephalon within 12 hr after Emx1‐Cre ‐mediated Aki2 deletion. In addition, other studies suggest that an important functional role for Aki2 occurs during rapid proliferation of cells in response to a stimulus (Komiya, Akiyama, Sakumoto, & Tashiro, ; Komiya et al, ; Tartey et al, ), consistent with our observations. In contrast, our knockdown experiments using shRNA against Aki2 in differentiating C2C12 cells did not cause any obvious cell death, and the presence of persistent tdTom‐positive cells in Aki2 SimKO mutants suggests that not all cells die when Aki2 is removed.…”
Section: Discussionsupporting
confidence: 92%
“…It is interesting to note that Akirin2 knockout in B cells using CD19-Cre leads to reduced Cyclin D1 and Cyclin D2 mRNA expression [17]. Although typically associated with cell cycle progression, Cyclin D1 has also been reported to have a role in promoting neurogenesis in spinal cord that is independent of its cell cycle role [43].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Akirin2 binds to BAF60 subunits, as well as NF-κB protein IκB-ζ, to mediate expression of proinflammatory genes in macrophages [16]. Additionally, in Akirin2 knockout B cells, Brg1 recruitment to several promoter targets is impaired [17]. The role of Akirin2 in coordinating gene expression via interactions with the BAF chromatin remodeling machinery is likely to be relevant to the cortical phenotypes we have observed here, as a spate of recent studies have uncovered a critical role for the BAF complex in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Due to its complexity, the vaccine-induced immune response is a focus of on-going research and further processes involved in the humoral immune response have been reported. 29,30 Immunological network structure and robustness Basically, intercellular signaling processes of immune cells are orchestrated by cytokines, chemokines, and cell surface receptors, while intracellular signaling processes are conducted by various signaling pathways (e.g., TLR or Janus Kinase (JAK)/Signal transducer and activator of transcription (STAT) signaling pathway). Gene regulatory networks control both intra-and intercellular processes.…”
Section: The Vaccine Induced Immune Response: a Network Of Networkmentioning
confidence: 99%